P115 A segmental LPS challenge study to investigate the pharmacodynamics of a TRPV4 antagonist (GSK2798745) in healthy participants. (12th November 2019) - Mole, S; Harry, A; Fowler, A; Hotee, S; Warburton, J; Waite, S; Beerahee, M; Behm, D; Badorrek, P; Müller, M; Faulenbach, C; Lazaar, A; et al.
Abstract : Introduction and objectives: Acute Respiratory Distress Syndrome (ARDS) is associated with increased pulmonary vascular permeability. In the lung, transient receptor potential vanilloid 4 (TRPV4), a Ca2+-permeable cation channel, is a known regulator of endothelial permeability and pulmonary oedema. Segmentally-instilled lipopolysaccharide (LPS) challenge was used as a surrogate injury model to investigate the effects of TRPV4 channel blockade on alveolar-septal barrier permeability. Methods: Healthy participants were randomised 1:1 to receive 2 doses of GSK2798745, a potent and selective TRPV4 channel blocker, or placebo, 12 h apart. The first and second doses were administered orally, respectively, 2 h before and 10 h after LPS instillation; LPS was administered by bronchoscopy. Total protein (TP) and neutrophils, as markers of barrier permeability and inflammation, were measured in bronchoalveolar lavage (BAL) samples collected before and after LPS challenge. The primary endpoint was baseline adjusted TP concentration in BAL at 24 h after LPS challenge. A Bayesian framework was used to estimate the posterior probability of any percentage reduction (GSK2798745 relative to placebo). Results: Forty-seven participants were dosed and 45 completed (22 on GSK2798745 and 23 on placebo). There was no significant effect of GSK2798745 on BAL TP or neutrophils (Table). Overall, GSK2798745 was safe and well tolerated. The study was terminated early after an interim analysis, based on 20 participants in each group; if the study had continued to completion, there was <7% probability of achieving success (defined as =>95% probability of any percentage reduction in BAL TP after GSK2798745). Conclusion: As expected, the dose regimen of GSK2798745 gave plasma levels predicted to provide ∼70–85% TRPV4 inhibition during the 24 h after LPS challenge. At that exposure, GSK2798745 did not affect segmental LPS-mediated elevation of BAL TP or neutrophils. This study does not support GSK2798745, at the exposures observed in this study, as a treatment for alveolar-septal barrier permeability in ARDS patients. ClinicalTrials. gov Identifier: NCT03511105